2019
DOI: 10.1016/j.brs.2019.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Combining reward and M1 transcranial direct current stimulation enhances the retention of newly learnt sensorimotor mappings

Abstract: Background Reward-based feedback given during motor learning has been shown to improve the retention of the behaviour being acquired. Interestingly, applying transcranial direct current stimulation (tDCS) during learning over the primary motor cortex (M1), an area associated with motor retention, also results in enhanced retention of the newly formed motor memories. However, it remains unknown whether combining these distinct interventions result in an additive benefit of motor retention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…In tDCS studies, there is evidence that changes in motor cortical excitability induced by M1 or SMA tDCS can have a positive effect on different aspects of motor learning, including explicit or implicit sequence learning and visuomotoradaptation tasks [18,15,19,20]. Reward-based motor learning, however, had not been the focus of tDCS investigations until recently [28]. This study demonstrated that combining reward signals with M1-tDCS could improve motor learning, as reflected in the retention of motor skills.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…In tDCS studies, there is evidence that changes in motor cortical excitability induced by M1 or SMA tDCS can have a positive effect on different aspects of motor learning, including explicit or implicit sequence learning and visuomotoradaptation tasks [18,15,19,20]. Reward-based motor learning, however, had not been the focus of tDCS investigations until recently [28]. This study demonstrated that combining reward signals with M1-tDCS could improve motor learning, as reflected in the retention of motor skills.…”
Section: Introductionmentioning
confidence: 74%
“…The outcome was, however, not entirely unexpected, as standard M1-tDCS protocols generally assess effects on motor retention or consolidation [43,19,44,15] and have so far not reported modulations of motor learning processes that depend on reward signals. One notable exception is a recent anodal tDCS study that used smaller electrodes anterior and posterior to M1 [28]. This work demonstrated a benefit of the combination of reward signals and M1-tDCS on motor retention during a motor adaptation paradigm.…”
Section: Role Of Frontopolar Cortex In the Intentional Modulation Of mentioning
confidence: 90%
See 3 more Smart Citations